KORELASI ANTARA IKLIM SOSIAL SEKOLAH TEMAN SEKELAS DAN GURU DENGAN KESEJAHTERAAN PSIKOLOGIS (WELL BEING) SISWA SEKOLAH DASAR - Muhammad Aldi Reinaldi; Dewi Fitriani; Yoesrina Vini Syafitri; Rakha Putra; Takwa Sandika (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Elementary school students require a supportive environment to achieve psychological well-being, yet educational practices frequently prioritize academic achievement while neglecting non-academic factors and mental health issues such as anxiety and bullying. To address this problem, this study aimed to empirically examine the correlation between school social climate specifically teacher support and peer support and the psychological well-being of elementary school students. This research utilized a quantitative correlational design. The population consisted of 35 sixth-grade students in Cimapag, Cireunghas, Sukabumi, from which a sample of 30 students was selected using simple random sampling techniques. Data were gathered through psychological scale instruments measuring teacher emotional support, peer acceptance, and six dimensions of psychological well-being, followed by bivariate and multivariate correlation analysis. The results indicated that the school social climate and student psychological well-being were generally perceived in the high and optimal categories. Furthermore, hypothesis testing revealed a statistically significant positive correlation between school social climate and psychological well-being, demonstrating that both teacher support and peer acceptance substantially contribute to fostering students' autonomy, psychological safety, and positive social relationships.